Theory of production: a long-period analysis - Kurz, Heinz D.; Salvadori, Neri (New York, 1997)
This compelling book contains a comprehensive analytical treatment of the theory of production in a long-period framework. Although the authors take a 'Classical' approach to their subject, the scope of investigation and methods employed should interest all economic theorists. Professors Kurz and Salvadori explore economic systems that are characterised by a particular kind of primary input in the production process, such as different kinds of labour and natural resources. These systems and the corresponding prices can be understood to reflect characteristic features of a capitalist market economy in an ideal way: they express the pure logic of the relationship between value and distribution in an economic system. Specific chapters deal with prices and income distribution, economic growth, joint production, fixed capital, scarce natural resources (both renewable and exhaustible), and heterogeneous labour. The historical origins of the concepts used are also discussed in considerable detail.
Keywords: Production